Mechanical and Self-Healing Performances of Crumb Rubber Modified High-Strength Engineered Cementitious Composites - Jiangtao, Yu; Fangming, Jiang; Qiong, Xing; Qi, Yang; Mi, Li (Frontiers in Materials, 2021)
High-strength engineered cementitious composite (HS-ECC) reinforced with polyethylene (PE) fiber characterizes larger crack width compared to that of the conventional polyvinyl alcohol fiber-reinforced ECC (PVA-ECC), weakening the self-healing potential of HS-ECC. Tailoring the properties of HS-ECC by introducing crumb rubber (CR) as artificial flaws can lower the matrix toughness and the crack width, leading to an enhanced self-healing potential of HS-ECC. In this study, CR is used to entirely replace silica sand (SS) with three equivalent aggregate to binder ratios of 0.2, 0.4 and 0.6, and two CR particle size (i.e., CR1 and CR2) is also considered to investigate the effects on density, compressive properties and tensile performances of HS-ECC. Although CR substitution of SS influences adversely on the mechanical strengths of HS-ECC, it can reduce the HS-ECC matrix fracture toughness and activate more microcracks and reduce crack width. Moreover, CR-modified HS-ECC specimens featuring with the smallest crack width pre-loaded to three specific strain levels, including 0.5%, 1.0% and 2.0% and then experienced wet-dry conditioning exhibit effective mechanical and non-mechanical properties recovery. The further hydration of binder materials enhances the interfacial bond stress and thus retains the mechanical performances of self-healed HS-ECC, which is expected to enlarge the practical application and benefit the sustainability of HS-ECC.